THE INFLUENCE OF WORK ENVIRONMENT AND ORGANISATIONAL CLIMATE ON JOB SATISFACTION AND ITS IMPLICATIONS ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN BOJONG DISTRICT, PANDEGLANG REGENCY - Maemunah Maemunah; Tata Rustandi; Angrian Permana (Yayasan Education and Social Center, 2026)
Teacher performance is a key factor in determining the quality of education. However, it is influenced not only by individual competence but also by organisational factors, such as the work environment, organisational climate, and job satisfaction. This study aims to examine the effects of the work environment and organisational climate on job satisfaction and their implications for teacher performance in public elementary schools in Bojong Subdistrict, Pandeglang Regency. This research employed a quantitative approach with an explanatory survey design. Data were collected via Likert-scale questionnaires distributed to 100 teachers and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results indicate that both the work environment and organisational climate have positive and significant effects on teachers' job satisfaction. Job satisfaction was found to be the most dominant factor influencing teacher performance and also functioned as a mediating variable linking organisational factors to performance. In addition, the work environment and organisational climate had direct, significant effects on teacher performance. These findings highlight the importance of strengthening organisational conditions in schools to improve teacher performance. This study contributes to the development of educational management research by providing an integrated model linking work environment, organisational climate, job satisfaction, and teacher performance.